Métodos de controle de cigarrinha-das-raízes da cana-de-açúcar (Mahanarva fimbriolata): uma revisão - Trapani, Gabriel Antônio (Universidade Federal de São Carlos, 2025)
In Brazil, sugarcane plays a crucial role in the economy, being widely cultivated for the production of sugar, ethanol, and other by-products, contributing significantly to job creation and regional development. However, the transition to mechanized harvesting and the prohibition of burning have resulted in an increased incidence of the root spittlebug, Mahanarva fimbriolata, making it a relevant pest for the sugarcane crop. The root spittlebug causes significant economic damage by sucking the sap from the plants, reducing their photosynthetic capacity and leading to a loss of productivity and quality of the raw material. The life cycle of this insect is influenced by climatic factors, with populations growing during the rainy season, to control the root spittlebug, integrated strategies are recommended, involving population monitoring, the use of less susceptible varieties, cultural management, chemical and biological control. The combination of different control methods increases the chances of success and reduces the economic and environmental impacts, promoting sustainable agricultural practices, the objective of this study was to explore different methods of controlling the root spittlebug in the sugarcane crop, considering viability, effectiveness, and sustainability. Changes in sugarcane production, biological aspects of the pest, management strategies described in the literature, as well as the importance of monitoring and using different control techniques to mitigate the damage caused by the root spittlebug in the sugarcane crop were discussed.
Control methods of the sugarcane spittlebug (Mahanarva fimbriolata): a review
Keywords: Controle cultural; Controle biológico; Controle químico; Controle varietal; Manejo integrado; Cultural control; Biological control; Chemical control; Varietal control; Integrated management; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE::ENTOMOLOGIA AGRICOLA